Efficacy of zinc oxide nanoparticles in attenuating pancreatic damage in a rat model of streptozotocin-induced diabetes. (1st November 2016) - Wahba, Nashwa S.; Shaban, Sahar F.; Kattaia, Asmaa A. A.; Kandeel, Sara A.
ABSTRACT: Zinc oxide nanoparticles (ZnO NPs) therapy is a promising strategy for treatment of several diseases. We aimed to investigate the therapeutic potential of ZnO NPs in ameliorating the histopathological and functional alterations in the pancreas of a rat model of streptozotocin-induced diabetes. Rats were randomized into control, diabetic and ZnO NPs-treated diabetic groups. Biochemical assays of blood glucose and serum insulin were performed. Pancreas specimens were processed for light and electron microscope examinations. ZnO NPs effectively reversed diabetes-induced pancreatic injury, as evidenced by the structural and ultrastructural improvement and confirmed by biochemical normalization of blood glucose and serum insulin.